2021
DOI: 10.1177/0963721421993116
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Parent Educational Attainment in Parenting and Children’s Development

Abstract: Socioeconomic status (SES)—indexed via parent educational attainment, parent occupation, and family income—is a powerful predictor of children’s developmental outcomes. Variations in these resources predict large academic disparities among children from different socioeconomic backgrounds that persist over the years of schooling, perpetuating educational inequalities across generations. In this article, we provide an overview of a model that has guided our approach to studying these influences, focusing partic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
76
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(91 citation statements)
references
References 29 publications
9
76
1
5
Order By: Relevance
“…The present study found that parental education had a stronger relationship with children’s cognitive school readiness than family income. This finding concurs with a number of previous studies, which found that parental education is a stronger predictor of children’s academic achievement than family income (e.g., Raviv et al, 2004 ; Davis-Kean, 2005 ; Erola et al, 2016 ; Gonzalez et al, 2017 ; Luo and Zhang, 2017 ; Davis-Kean et al, 2021 ). For instance, parents’ education level accounted more variance of children’s early academic skills than family income ( Vasilyeva et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study found that parental education had a stronger relationship with children’s cognitive school readiness than family income. This finding concurs with a number of previous studies, which found that parental education is a stronger predictor of children’s academic achievement than family income (e.g., Raviv et al, 2004 ; Davis-Kean, 2005 ; Erola et al, 2016 ; Gonzalez et al, 2017 ; Luo and Zhang, 2017 ; Davis-Kean et al, 2021 ). For instance, parents’ education level accounted more variance of children’s early academic skills than family income ( Vasilyeva et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…These findings suggest that the positive effects of authoritative parenting may be mediated by more specific parenting behaviors ( Patterson and Yoerger, 1991 ). Nevertheless, most of the existent research has focused either on parenting style or on parental involvement separately ( Mistry et al, 2002 ; Sonnenshein and Munsterman, 2002 ; Aram and Levin, 2004 ; Davis-Kean et al, 2021 ). There is a need to consider authoritative parenting and parental involvement simultaneously in examining children’s school performance.…”
Section: Introductionmentioning
confidence: 99%
“…Mother's educational attainment (our chosen indicator of SES) has been found to be strongly associated with children's pre-academic skills (Duncan and Magnuson, 2003;Nguyen et al, 2016;Davis-Kean et al, 2021). Our findings agree with much of the extant literature in showing that SES significantly predicts mathematics on entry to primary school, even after controlling for prior math achievement, EF and BSR.…”
Section: Contributions Of Ses Ef and Bsr To Math Achievement At P1supporting
confidence: 83%
“…In the studies reviewed above, SES was measured either using single indicators (e.g., household income) or composite measures (e.g., combination of income and parental education). A growing body of evidence points to parental education attainment as the most powerful predictor of children's cognitive and academic outcomes (Magnuson et al, 2009;Harding et al, 2015;Davis-Kean et al, 2021;Waters et al, 2021). More educated parents tend to have access to a greater number of resources and provide their children with more stimulating activities, toys, books, and educational opportunities both in and outside the home (Cebolla-Boado et al, 2017;Davis-Kean et al, 2021).…”
Section: Self-regulation Skills As Mediators Between Ses and Math Achievementmentioning
confidence: 99%
See 1 more Smart Citation